Tanggungjawab Hukum Pelaku Pendistribusian Konten Pornografi Melalui Media Sosial ( Studi Kejaksaan Sukoharjo) - Lestari, Tri Indah; Agus Santoso, Aris Prio (IAIN Metro, 2024)
Advances in information and communication technology have given birth to many things, one of which is social media, using mobile phones or devices that can access the internet. This convenience has positive and negative impacts where everything is made easier with consequences including negative things that become easier and give birth to new types of crime as time goes by and which is very close and often becomes a topic of debate, namely pornographic content on the internet, including social media today. Misuse of the function of electronic media has become a rapid medium causing the spread of content containing decency to increase day by day. This research aims to determine the legal responsibility of perpetrators of distributing pornographic content via social media (Sukoharjo Prosecutor's Study) as well as the form of legal protection for victims resulting from the distribution of pornographic content via social media (Sukoharjo Prosecutor's Study). This research will use normative juridical research methods which are descriptive analytical in nature using secondary data in the form of legal materials. The result of the discussion is that the sentence is punishable by a maximum imprisonment of 6 years and/or a fine of Rp. 1,000,000. and the authorities provide legal protection and rehabilitation for victims.